2020
DOI: 10.1002/ceat.201900511
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Estimation for Incompressible Cake Filtration: Advantages of a Modified Fitting Method

Abstract: There is a widely used linear strategy to determine the parameters specific cake resistance and filter medium resistance in incompressible cake filtration. In this article, it is intended to demonstrate that this strategy has some disadvantages and should be replaced by an alternative nonlinear approach which yields more exact results. Even though the gains in precision are small for most cases, the nonlinear strategy is favored because it involves no extra effort and is grounded in the same physical theory as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, recent research conducted by Kuhn et al 24 effectively showed that fitting the filtration curve nonlinearly to a root function is more precise both in terms of execution and results. Thus, the change in filtrate volume over time is described as: trueV= 2Δp A2 η αnormalK k t+ ( RnormalM A αnormalK k )2 - RnormalM A αnormalK k …”
Section: Methodsmentioning
confidence: 99%
“…However, recent research conducted by Kuhn et al 24 effectively showed that fitting the filtration curve nonlinearly to a root function is more precise both in terms of execution and results. Thus, the change in filtrate volume over time is described as: trueV= 2Δp A2 η αnormalK k t+ ( RnormalM A αnormalK k )2 - RnormalM A αnormalK k …”
Section: Methodsmentioning
confidence: 99%